Circular oscillating laser melting deposition of nickel-based superalloy reinforced by WC: Microstructure, wear resistance and electrochemical properties. (August 2021) - Xia, Yelin; Chen, Hanning; Liang, Xiaodan; Lei, Jianbo
Abstract: Circular oscillating laser was used to deposit GH3536 nickel-based superalloy, GH3536-16 wt.% coarse WC and GH3536-16 wt.% fine WC composite. The microstructure characteristics and evolution, phase composition and properties of the three materials fabricated by circular oscillating laser melting deposition were studied. In the mode of circular oscillating laser, equiaxed and columnar crystal structures are formed in the middle and edge of the cladding track of the three materials due to its temperature gradient distribution and the laser stirring effect on molten pool. The main phases of the composite coatings are γ-Ni solid solution, WC, W2 C and M6 C. WC particles uniformly distributed in GH3536 matrix have the effects of fine grain strengthening and dispersion strengthening. Compared with GH3536, the average microhardness of the composite material is increased by 59.70% (coarse WC) and 74.66% (fine WC) respectively, and the wear rate is reduced by 84.87% (coarse WC) and 89.17% (fine WC) respectively. The wear mechanism changes from adhesive wear to abrasive wear after adding WC. The corrosion current density of the composite coating is 44.9% (coarse WC) and 26.5% (fine WC) lower than that of GH3536, respectively. WC particles have physical shielding and solid solution strengthening effects, and improve the corrosion resistance of GH3536 coating.